Decentralized School Management in Government Schools in Nepal: Policy for Quality Improvement - Paudel, Janardan; Pokharel, Anil Kumar (HISAN: Journal of History Association of Nepal, 2022)
This research article gives a holistic view of the status of school management committee in our country. Education is one of the basic needs of human beings which has brought changes all over the world. Today, we are around the formal schooling system for which school level is the first step. We are also in the hold of globalization of education and social structure for which we have to compete globally for employment. In such situation, the system and management of education should be of global standard. School management has been a kind of burning issue at the present situation in education system. The state has to follow the trends of decentralization of education. But in Nepal, there is fully centralized education system. Due to this reason, it is thought that the state is the only responsible body for overall education sector. The SMC members are not fully authentic bodies in Nepalese schools. They have no more interest about the problems related to school. They are mostly politically related and also there is absence of true guardianship of SMC members. Most of the SMC members' children do not study in public schools but they are selected with political sources. As a whole school management committee has not supported for the improvement of teaching learning activities. They have no any plan to raise funds and support the school. Most of the children in public schools are also from lower class people. The guardians also cannot support their children by providing necessary things. As a consequence, the SLC result of public schools is very poor except some rare cases. SMC members are not found capable of taking management responsibility of schools. The state also has not fixed any criteria to become SMC members. This research study has found clear obstacle in education system of the politicalized group in management sector. Political interference should not be given emphasis and priority in education sector. Moreover, politics in education sector should be strongly discouraged to make public sector responsible towards school management in public schools in Nepal. This research study tries to reply the research question “What type of management at schools should be developed to improve the quality of education?” The general objective of this study is to analyse the overall status of the school management committee (SMC) in public schools in Nepal.